Does working capital management matter? A comparative case between consumer goods firms and construction firms in Vietnam - Thi Quy Vo; Ngoc Cuong Ngo (Cogent Business & Management, 2023)
AbstractThis study investigates the effects of working capital management (WCM) through and its components (Days Sales Outstanding—DSO, Days Inventory Outstanding—DIO, and Days Payable Outstanding—DPO and Net Working Capital) on firm profitability in consumer goods and construction firms by applying Generalized Method of Moments (GMM). The independent samples t-test was used to study the difference of WCM between the two groups of firms. The data were collected from 21 consumer goods firms and 41 construction firms listed on Vietnam Stock Market in the period 2011–2020. This study indicates that WCM components impact differently on firm profitability of selected firms in the sample. The results provided empirical evidence supporting financial management theory and implied that WCM is a critical factor explaining firm profitability, and industry specificity is a factor explaining the difference in WCM and its influence on firm profitability in the study sample. The results recommend that financial managers should focus on managing working capital and consider industry characteristics as developing working capital management policy to improve firm profitability.